Acid-resistant genes of oral plaque microbiome from the functional metagenomics - Zhang, Meng (J Oral Microbiol, 2018)
Acid resistance is one of key properties assisting the survival of cariogenic bacteria in a dental caries environment, but only a few genes conferring acid resistance have been identified to data. Functional metagenomics provides a systematic method for investigating commensal DNA to identify genes that encode target functions. Here, the host strain Escherichia coli DH10B and a constructed bidirectional transcription vector pSKII(+)-lacZ contributed to the construction of a metagenomic library, and 46.6 Mb of metagenomic DNA was cloned from carious supragingival plaque of 8children along with screening for lethal functionality. The screen identified 2 positive clones that exhibited a similar aciduric phenotype to that of the positive controls. Bioinformatic analysis revealed that these two genes encoded an ATP/GTP-binding protein and a malate dehydrogenase. Moreover, we also performed functional screening of Streptococcus mutans, since it is one of the predominant cariogenic strains but was not identified in our initial screening. Five positive clones were retrieved. In conclusion, our improved functional metagenomics screening method helped in the identification of important acid resistance genes, thereby providing new insights into the mechanism underlying caries formation as well as in the prevention and treatment of early childhood caries (ECC).